Chaunus ictericus (Spix, 1824) as paratenic host of the giant kidney worm Dioctophyme renale (Goeze, 1782) (Nematoda: Enoplida) in Sao Cristovao district, Tres Barras county, Santa Catarina state, Brazil - Pedrassani, Daniela [UNESP]; Lux Hoppe, Estevam Guilherme; Tebaldi, Jose Hairton [UNESP]; Nascimento, Adjair Antônio do [UNESP] (Elsevier B.V., 2009)
Dioctophyme renale larvae have been found in cysts in the gastric wall of 5.17% (3/58) Chaunus ictericus specimens from Sao Cristovao district, Tres Barras municipality, Santa Catarina state, Brazil. However, larvae of this nematode were not found in sympatric Chaunus schneideri. The larvae caused a mild granulomatous reaction. This is the first report of paratenic hosts for D. renale in Brazil, and probably is also the first in the Neotropical region. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Dioctophyme renale; Larvae; Morphology; Chaunus ictericus; Chaunus schneideri; Paratenic hosts